2021
DOI: 10.1186/s13287-021-02642-w
|View full text |Cite
|
Sign up to set email alerts
|

Bone regeneration in rat calvarial defects using dissociated or spheroid mesenchymal stromal cells in scaffold-hydrogel constructs

Abstract: Background Three-dimensional (3D) spheroid culture can promote the osteogenic differentiation of bone marrow mesenchymal stromal cells (BMSC). 3D printing offers the possibility to produce customized scaffolds for complex bone defects. The aim of this study was to compare the potential of human BMSC cultured as 2D monolayers or 3D spheroids encapsulated in constructs of 3D-printed poly-L-lactide-co-trimethylene carbonate scaffolds and modified human platelet lysate hydrogels (PLATMC-HPLG) for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 74 publications
0
31
0
Order By: Relevance
“…Compared to our study, these authors reported much lower bone formation (30%) using micro-CT analysis after 2 months of implantation Another study evaluated bone regeneration of cell-free poly- l -lactide- co -trimethylene carbonate scaffolds combined with modified human platelet lysate hydrogels implanted in rat calvarial defects. The results revealed that about 15% bone regeneration was obtained after 2 months of implantation by using in vivo CT-scanning technique . Even after 3 months, they could not achieve the same bone formation as observed herein, with the increase being around 43.2% only.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Compared to our study, these authors reported much lower bone formation (30%) using micro-CT analysis after 2 months of implantation Another study evaluated bone regeneration of cell-free poly- l -lactide- co -trimethylene carbonate scaffolds combined with modified human platelet lysate hydrogels implanted in rat calvarial defects. The results revealed that about 15% bone regeneration was obtained after 2 months of implantation by using in vivo CT-scanning technique . Even after 3 months, they could not achieve the same bone formation as observed herein, with the increase being around 43.2% only.…”
Section: Discussionmentioning
confidence: 54%
“…Hydrogels and scaffolds have been used independently over the last two decades with their own lion’s share of advantages and shortcomings. Poor hydrogel mechanical strength makes them fail easily under the heavy loads usually present in the native bone, and the substantially harder porous scaffolds do not offer a native-like environment for cells to thrive within, resulting in insufficient bone formation. Combining the two into a single material could enable a trade-off to maintain their respective advantages while overcoming their shortcomings when used alone. , For these reasons, scaffold–hydrogel systems should be at the very heart of the field in terms of recreating hard bone-like tissues. Unfortunately, only a few studies have examined the performance of these in vivo animal studies , with poor outcomes accounting for a bone healing efficiency of about 5–45% , after 1 month or 10.6–29.2% , after 2 months. Indeed, even though mechanical requirements for optimal bone healing are fulfilled in the abovementioned studies, they did not mimic the complex hierarchical architecture of the native microenvironment, which contains features ranging from nanometer to micrometer, as well as the combinatorial chemistry of the mineral deposits within the native bone.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonate scaffolds with hydrogel structures offer promising scaffolds for bone tissue engineering applications, regardless of monolayer or spheroid cell culture [ 23 ]. In contrast to two-dimensional dedifferentiated fat cells, three-dimensional dedifferentiated fat spheroid promoted osteogenic differentiation and bone formation via canonical Smad 1/5 signaling pathways, according to research comparing the in vitro osteogenic potential of rat dedifferentiated fat cells cultured under osteogenic conditions in three-dimensional spheroids with that in two-dimensional monolayers [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bone regeneration process was accelerated in vivo by neurosphere medium spheroids created under modified neurosphere culture conditions with constant shaking [ 25 ]. In contrast, constructions using two-dimensional and three-dimensional bone marrow mesenchymal stem cells behaved comparably in vivo despite a tendency for improved in vitro calcification [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the 3D cell culture must be able to simulate the main characteristics of the in vivo environment, including the interactions between cells and the extracellular matrix, between cells and organs, and between cells and other cells, in order to better realize the morphology and function of cells in vitro, understand their physiological function, and establish extensive cell-to-cell and cell-to-extracellular matrix (ECM) interactions [ 191 ]. At present, studies have confirmed that a 3D culture of stem cells with microspheres can efficiently promote the growth of stem cells as well as osteogenic and chondrogenic differentiation [ 192 , 193 ], and promote the paracrine ability of stem cells. This causes more anti-inflammatory factors and nutritional factors (such as VEGF, PDGF and FGF) to be expressed, thus allowing stem cells to play a more effective therapeutic role in bone regeneration [ 194 ].…”
Section: Novel Applications Of Microspheres For Bone Tissue Engineeringmentioning
confidence: 98%